ANALYSIS OF THE REPRESENTATION OF HAPPINESS EMOTIONS IN DINDAPS' DIGITAL ILLUSTRATIONS ON INSTAGRAM - Ashwa Dzikria; Farah Yumna Salma Flastica; Aghnia Nur Syahida; Najla Khafifah Fadhilah; Aliyah (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the representation of happiness emotions in digital illustrations by Dinda Puspitasari (@dindaps) published on Instagram. Dinda Puspitasari is a Jakarta-based digital illustrator widely recognized at the national and international level, having collaborated with clients such as Dior, Adidas, Spotify, and Victoria's Secret. This research employs a descriptive qualitative approach using Roland Barthes' semiotic analysis method to examine the denotative, connotative, and mythological meanings embedded in the visual elements of her illustrations. The research focuses on three selected illustrations that explicitly represent happiness themes. The analysis reveals that Dinda Puspitasari represents happiness emotions through the use sof warm and vibrant color palettes such as yellow, pink, and peach; cheerful facial expressions of illustrated figures; decorative elements such as flowers and positive everyday objects; and a playful, feminine visual style. This study is expected to contribute to the academic discourse on Indonesian digital illustration from a Visual Communication Design perspective.